Optimizing Supplier Data Management Using Decision Trees at Bambu Makmur Jaya Store - Lidia Terecia; Sandy Kosasi (Computer Science Research and Its Development Journal, 2024)
he challenge faced by craft stores in the era of digitization is the difficulty in choosing the right suppliers, resulting in unstable product availability and uncompetitive prices. Inefficient supplier selection can also disrupt the supply chain and overall business performance. The objective of developing a supplier data system software using Decision Trees is to enhance supplier selection optimization, ensure the best product quality, and improve decision-making quality. The solution design method used is Extreme Programming (XP), focusing on forming small teams. Testing is conducted using white-box methods that meet functional requirements for several software features. The result of this research is the development of a supplier data website software for Bambu Makmur Jaya store using the Laravel framework. It aims to assist Bambu Makmur Jaya store owners in easily viewing supplier and product recommendations, ensuring warranty deadlines are not missed through real-time notifications, and providing positive impacts in applying technology to business, as well as efficiency in supplier data processing and inventory management.